Global, regional and national burdens of cardiovascular disease attributable to secondhand smoke from 1990–2019: an age-period-cohort analysis - Hong Jiang; Xiang-Bin Pan; Xiaofei Li; Shouzheng Wang; Zeye Liu; Peijian Wei; Fengwen Zhang; Wen-Bin Ou-yang (Open Heart)
Background Over the past three decades, significant disparities in the global burden of cardiovascular disease (CVD) have been observed, particularly CVD attributed to secondhand smoke. However, a comprehensive understanding of global trends and their interaction with secondhand smoke remains inadequate.Methods Using Global Burden of Disease data (1990–2019), an age-period-cohort analysis examined temporal trends in CVD mortality among secondhand smoke-exposed populations, considering age, period and cohort interactions.Results Over the 30-year period, the global number of CVD deaths attributed to secondhand smoke increased substantially, from 432.6 thousand in 1990 (95% UI: 357.4–508.3) to 598.5 thousand in 2019 (95% UI: 489.7–713.5), representing a 38.4% increase (95% UI: 26.8%–49.5%). In 2019, CVD accounted for 45.9% of all deaths attributable to secondhand smoke among both sexes globally. Among these CVD deaths, ischaemic heart disease predominated, accounting for 66.4% of cases, compared with stroke. The distribution by sex revealed a slightly lower percentage of males (46.5%) than females (53.5%). Age-period-cohort models show overall global decline in CVD mortality due to secondhand smoke over 30 years, with regional, sex and subtype variations. Notably, a higher Sociodemographic Index (SDI) correlated with a greater reduction in mortality, exhibiting a significant 39.1% decrease in high SDI areas (95% UI: 35.6%–42.3%), in stark contrast to the minimal change observed in low SDI areas (0.1%, 95% UI: −52.4%–62.2%).Conclusions This study highlights the importance of considering secondhand smoke as a modifiable CVD risk. Further research is needed to understand disparities in CVD burden across development levels, sexes and subtypes.